Waginizm jako przyczyna nieważności małżeństwa w świetle kan. 1084 KPK z 1983 r. - Wybult, Witold (Ius Matrimoniale, 2017)
Sexual disorders of women are a broad problem contended by many specialists of different disciplines. Vaginismus is one of the diseases of this type. It is a disorder hampering or making the sexual intercourse impossible. By virtue of the cause, it may appear in two types: as organic and inorganic i.e. psychogenic vaginismus. On the basis of the canon law a vaginismus can become a cause of the marital impediment or the inability for assuming substantial conjugal duties. In case of organic vaginismus (always when woman lacks vagina), whether or not this lack was replaced with the artificial vagina or not, the woman shall be recognized as impotent. Thus, marriage entered by her (assuming that the requirements of pre-existence, permanence and certainties are met) is void. The same applies to the case of the underdevelopment of the vagina. However, talking about psychogenic vaginismus the distinction shall be made between their different stages (most difficult, heavy, less difficult and light cases). In first three cases we are dealing with the situation when the woman certainly isn’t able to co-exist and to accept ejaculate. Therefore, an obstacle of impotence exists. In fourth however, the situation can look in two ways depending on the individual case. Irrespective of that, by virtue of the high percentage of vaginismus effective curing, some of the specialists indicate that nowadays the existences of impotence obstacle is in decline.